Environmental oestrogens cause predation-induced population decline in a freshwater fish. Issue 10 (31st October 2018) - Rearick, Daniel C.; Ward, Jessica; Venturelli, Paul; Schoenfuss, Heiko
Abstract : Understanding population-level effects of environmental stressors on aquatic biota requires knowledge of the direct adverse effects of pollutants on individuals and species interactions that relate to survival and reproduction. Here, we connect behavioural assays with survival trials and a modelling approach to quantify changes in antipredator escape performance of a larval freshwater fish following exposure to an environmental oestrogen, and predict changes in population abundance. We quantified the effects of short-term (21 days) exposure to 17β-oestradiol (E2) on the antipredator escape performance of larval fathead minnows ( Pimephales promelas ) and the probability of predation by a natural predator, the bluegill sunfish ( Lepomis macrochirus ). Compared with unexposed minnows, minnows exposed to environmentally relevant concentrations of E2 that approach total oestrogenic activity of wastewater-dominated environments (38 and 103 ng l −1 ) had delayed response times and slower escape speeds, and were more susceptible to predation. Incorporating these data into a stage-structured population model demonstrated that enhanced predation mortality at the larval stage can result in population declines. These results indicate that subtle, sub-lethal shifts in the behaviour of individuals due to human-mediated environmental change can impact species interactions with measurable population-level effects. Such changes have the potential to alter higher-order trophic interactions and disrupt aquatic communities.